1971
DOI: 10.7164/antibiotics.24.443
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Sensitivity of Mycoplasmas Isolated From Various Animals and Sewage to Antibiotics and Nitrofurans

Abstract: A total of 15 strains of Mycoplasmawere examined for in vitro sensitivity to 22 commonly used antibiotics and 9 nitrofurans. They were strains of Mycoplasma mycoides var. mycoides, M. mycoides var. capriy M. hyorhinis, M. suipneumoniae (hyopneumoniae), M. granularum, M. cams, M. pulmonis, M. arthritidiSy M. neurolyticum, M. gallisepticum, and M. laidlawii, all of which were isolated from various animals, except for one strain of M. laidlawii which was isolated from sewage. The sensitivity was determined by obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
56
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 23 publications
0
56
0
Order By: Relevance
“…In addition, M. hyopneumoniae and M. hyorhinis strains were resistant to cephaloridine and cephalothin but susceptible to furazolidone; the M. hyopneumoniae strains were susceptible, and M. hyorhinis was resistant, to oleandomycin. Our strains of M. hyopneumoniae and M. hyorhinis were susceptible to erythromycin, but Ogata et al (8) found some strains to be resistant. Strains of M. hyopneumoniae, as tested, were resistant to ampicillin, methicillin sodium, and penicillin.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…In addition, M. hyopneumoniae and M. hyorhinis strains were resistant to cephaloridine and cephalothin but susceptible to furazolidone; the M. hyopneumoniae strains were susceptible, and M. hyorhinis was resistant, to oleandomycin. Our strains of M. hyopneumoniae and M. hyorhinis were susceptible to erythromycin, but Ogata et al (8) found some strains to be resistant. Strains of M. hyopneumoniae, as tested, were resistant to ampicillin, methicillin sodium, and penicillin.…”
mentioning
confidence: 88%
“…Strains of M. hyopneumoniae, as tested, were susceptible to kanamycin, but Ogata et al (8) found strains to show some resistance to the agent, with a MIC of 20 ,ug/ml. In addition, M. hyopneumoniae and M. hyorhinis strains were resistant to cephaloridine and cephalothin but susceptible to furazolidone; the M. hyopneumoniae strains were susceptible, and M. hyorhinis was resistant, to oleandomycin.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The uorine atoms of the disorderd CF 3 -group were located on a di erence Fourier map and re ned freely. chemistry as pharmacophores or auxophores possessing diverse pharmacological activities, including antibacterial [1][2][3][4][5], anticancer [6][7][8][9][10], antiviral [11][12][13], antihypertensive [14,15], anti-in ammatory [16,17] and antioxidant [18] activities. In addition, some 1,3,4-oxadiazoles are currently used as safe herbicides for crop protection [19][20][21].…”
Section: Methodsmentioning
confidence: 99%